2017
DOI: 10.1055/s-0043-108761
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinol Alleviates Osteoporosis and Myopathy in Glucocorticoid-Treated Rats

Abstract: Tanshinol is a major water-soluble active component of . In this study, we aimed to investigate whether tanshinol has potential therapeutic effects against glucocorticoid-induced osteoporosis and glucocorticoid-induced myopathy. Ninety-six female Sprague-Dawley rats were randomly assigned to five groups: a control group, a model group, and three model groups treated with 25 or 50 mg/kg of tanshinol, or calcitriol. All model groups received prednisone acetate for 90 days to induce glucocorticoid-induced osteopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…Only 25.81% ( n = 8) [28, 32, 35, 38, 39, 43, 46, 50] performed measurement of inflammatory markers, and the most cited parameters were Ca +2 content and serum alkaline phosphatase. Only 25.81% ( n = 8) [22, 32, 37, 38, 42, 46, 48, 49] reported whether the fracture had complete, partial, or absent closure. Other analyses related to bone strength, tensile strength, and expression of inflammatory genes that stimulate bone formation and osteogenic differentiation were performed in 38.71% ( n = 12) of the studies [20, 23, 24, 28, 33, 36, 40–42, 44, 45, 47] (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Only 25.81% ( n = 8) [28, 32, 35, 38, 39, 43, 46, 50] performed measurement of inflammatory markers, and the most cited parameters were Ca +2 content and serum alkaline phosphatase. Only 25.81% ( n = 8) [22, 32, 37, 38, 42, 46, 48, 49] reported whether the fracture had complete, partial, or absent closure. Other analyses related to bone strength, tensile strength, and expression of inflammatory genes that stimulate bone formation and osteogenic differentiation were performed in 38.71% ( n = 12) of the studies [20, 23, 24, 28, 33, 36, 40–42, 44, 45, 47] (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…(Lamiaceae; Y. Yang et al, ). Pharmacological researches have demonstrated that TAN exerts multiple beneficial biological activities, such as antioxidation (Y. Yang et al, ), antiliver fibrosis (Peng et al, ), antiosteoporosis (Chen et al, ), antiatherosclerosis (Song, Pu, & He, ), and anti‐inflammation (Y. Yang et al, ). In terms of anti‐inflammatory activity, Y. Yang et al () reported that TAN inhibited inflammatory response in a rat model of vascular dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier reports have shown that SAA stimulates osteogenesis and depresses adipogenesis in BMSCs both in vitro and in vivo. 15,16,43 Specifically, SAA attenuates the impairment of bone formation, bone loss, and bone quality deterioration elicited by glucocorticoid-mediated KLF15/WNT signalling and suppresses the glucocorticoid-induced oxidative stress and subsequent cell apoptosis associated with the KLF15/p66Shc signalling cascade. 17 Yang et al confirmed the protective effects of SAA on oxidative stress and its signalling pathways in osteoblastic differentiation.…”
Section: Dovepressmentioning
confidence: 99%
“…Several studies have shown that SAA stimulates osteogenesis and angiogenesis by regulating WNT signalling and oxidative stress. [14][15][16][17][18] However, the specific mechanism of SAA employed to accelerate fracture healing has not yet been fully elucidated. Relatively few studies have focused on the role of chondrogenesis, which involves the formation of cartilage that facilitates an initial union of most long bone fractures, 6,19 or endochondral ossification, which plays a vital role in the process of bone tissue repair during long bone fracture.…”
Section: Introductionmentioning
confidence: 99%